Proses Pembentukkan Gairaigo dalam Buku Teks Minna no Nihongo: Kajian Morfologi - Yani, Damai (Universitas Muhammadiyah Yogyakarta, 2018)
Abstract Gairaigo is a Japanese vocabulary written in katakana letters. Gairaigo is a special vocabulary, although the words derived from a foreign language but if they are used in Japanese language, they must be appropriated with the rules in the Japanese pronunciation and writing procedures. The data in this research taken from minna no nihongo shokyu I textbook. There are 97 gairaigo in the minna no nihongo shokyu I, but this paper only explains the formation of gairago. There are three morphological process of gairaigo that can be found in this research. First, gairaigo which is formed by affixation process. Second, gairaigo which is formed by compounding process and third gairaigo which is formed by abbreviation process. Clipping and contraction (karikomi) are included in the abbreviation process. To explain the morphological process of gairaigo, this research used theory by sutedi and tsujimura. This research is qualitative research with descriptive methode.